A Case of Endovascular Stent Graft Repair for Traumatic Thoracic Aortic Aneurysm in a Young Patient with Multiple Injuries - Hirano, Tadanori; Hioki, Iwao; Kinoshita, Toshihiko; Kato, Noriyuki; Mizumoto, Toru; Fujii, Hideki (Japanese Journal of Cardiovascular Surgery, 2004)
A 16-year-old boy with multiple injuries suffered in a motorcycle accident was admitted to our hospital. On admission, X-ray films showed left hemothorax and bone fractures of the left humerus, thigh bone, and pelvis. Computed tomography of the chest revealed a pseudoaortic aneurysm approximately 6.0cm in diameter at the proximal portion of the descending aorta. Because of multiple severe associated injuries, we considered that conventional aortic repair in the acute phase would be difficult. We therefore performed an endovascular stent-graft treatment 140 days after injury. The postoperative course was uneventful and the pseudoaneurismal sac has confirmed to decrease. Transluminal placement of endovascular stent-graft is a technically feasible method for treatment of traumatic aortic aneurysm. However, because the long-term results are still unknown, we should follow-up carefully, particularly in young patients.